PENERAPAN BAURAN PEMASARAN 7P DALAM MENGUKUR KEPUASAN KONSUMEN KERIPIK BUAH DARSA DI BANDAR LAMPUNG - Nuni Anggraini; Maria Ulfah; Varingan Prianando Tambunan (Politeknik Negeri Lampung., 2024)
This study aims to determine the level of customer satisfaction and the relationship between the importance and performance attributes of Darsa Fruit Chips consumers. This research was conducted in 5 gift shops that partnered with Darsa fruit chips in Bandar Lampung. The selection of this location was carried out purposively, with the consideration that the five souvenir shops had become partners of fruit chips for more than 1 year. The number of respondents taken was 50 people with 10 respondents each in each shop. The research time will be carried out from April to September 2023. The analysis used for customer satisfaction is using the Customer Satisfaction Index (CSI) or customer satisfaction index. To analyse how the relationship of an attribute's importance and its performance level (performance) is used Important Performance Analysis (IPA) method. The results obtained are the level of consumer satisfaction with Darsa Fruit chips classified into the category of very satisfied with the average level of conformity for all attributes on Importance Performance Analysis (IPA) is 98.12%. Some attributes are included in quadrant I, namely the Product, Place and Physical Evidence attributes, making these attributes require special attention for Darsa Fruit chips producers to increase the level of consumer satisfaction of Darsa Fruit chips